The Effect of Intellectual Capital and Islamicity Performance Index on the Financial Performance of Islamic Banks Registered with the OJK from 2021 to 2024 - Satari, Nadila Rahma; Eliyanora, Eliyanora; Oliyan, Fitra (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Indonesia has great potential to develop the Islamic banking sector. However, the instability of profitability levels in recent years and competition with conventional banks remain the main challenges currently facing Islamic banking. To address these, Islamic banks need to create competitive advantages and ensure their operations align with Islamic principles. This study aims to analyze the influence of Intellectual Capital and the Islamic Performance Index on the Financial Performance of Islamic Banks registered with the OJK during the period 2021-2024. This study uses a quantitative research method and a population comprising all Sharia Commercial Banks registered with the OJK from 2021 to 2024. Data were collected through purposive sampling, resulting in the selection of 10 Sharia Commercial Banks and 35 observations, and analyzed using panel-data regression in Stata 17. The results show that Intellectual Capital positively affects Financial Performance. In contrast, Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, and Islamic Income vs Non-Islamic Income do not have a significant effect on Financial Performance.